Exploration of Public Perception Factors Preservation Ecoculture (Case Study: Tamkesi and Sonaf Raja Oelolok Traditional Villages ) - Selviana Manek; Amiluhur Soeroso; Nur Widiyanto; Moch. Nur Syamsu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to analyze community perception of the preservation of the cultural ecology of the Tamkesi Traditional Village and Sonaf Raja Oelolok as a heritage tourism destination in North Central Timor Regency. The method used was quantitative research method with Exploratory Factor Analysis (EFA) approach with Varimax rotation technique to identify the factor structure of the 20 variables studied . The results of the analysis showed that the variables can be grouped into main factors , namely : (1) Social - Economic Interaction , which showed the link between cultural values and economic potential in encouraging preservation ; (2) Social - Environmental Awareness , reflecting the collective commitment of the community in maintenance cultural heritage and the environment ; (3) Perception - Economy , showed that the importance of community expectations of economic benefits from tourism as a driver of support for cultural preservation .These​ three factors significantly shape community perception and interact with each others in support the preservation of ecoculture as a foundation in the preservation of cultural ecology in the Traditional Village of Tamkesi and Sonaf King Oelolok , North Central Timor Regency.